Bevacizumab, carboplatin, and paclitaxel in the first line treatment of advanced ovarian cancer patients: the phase IV MITO-16A/MaNGO-OV2A study. Issue 6 (30th April 2021) - Daniele, Gennaro; Raspagliesi, Francesco; Scambia, Giovanni; Pisano, Carmela; Colombo, Nicoletta; Frezzini, Simona; Tognon, Germana; Artioli, Grazia; Gadducci, Angiolo; Lauria, Rossella; Ferrero, Annamaria; Cinieri, Saverio; et al.
Abstract : Objective: To explore the clinical and biological prognostic factors for advanced ovarian cancer patients receiving first-line treatment with carboplatin, paclitaxel, and bevacizumab. Methods: A multicenter, phase IV, single arm trial was performed. Patients with advanced (FIGO (International Federation of Gynecology and Obstetrics) stage IIIB-IV) or recurrent, previously untreated, ovarian cancer received carboplatin (AUC (area under the curve) 5), paclitaxel (175 mg/m 2 ) plus bevacizumab (15 mg/kg) on day 1 for six 3-weekly cycles followed by bevacizumab single agent (15 mg/kg) until progression or unacceptable toxicity up to a maximum of 22 total cycles. Here we report the final analysis on the role of clinical prognostic factors. The study had 80% power with a two-tailed 0.01 α error to detect a 0.60 hazard ratio with a factor expressed in at least 20% of the population. Both progression-free and overall survival were used as endpoints. Results: From October 2012 to November 2014, 398 eligible patients were treated. After a median follow-up of 32.3 months (IQR 24.1–40.4), median progression-free survival was 20.8 months (95% CI 19.1 to 22.0) and median overall survival was 41.1 months (95% CI 39.1 to 43.5). Clinical factors significantly predicting progression-free and overall survival were performance status, stage, and residual disease after primary surgery. Neither baseline blood pressure/antihypertensive treatment nor the development of hypertension during bevacizumab were prognostic. There were two deaths possibly related to treatment, but no unexpected safety signal was reported. Conclusions: Efficacy and safety of bevacizumab in combination with carboplatin and paclitaxel and as maintenance were comparable to previous data. Hypertension, either at baseline or developed during treatment, was not prognostic. Performance status, stage, and residual disease after primary surgery remain the most important clinical prognostic factors. Trial registration number: EudraCT 2012-003043-29; NCT01706120 .